De engenheiro a professor: a construção da profissionalidade docente. - Vaz, Jhonnes Alberto (2016)
This study aimed to investigate how the teacher engineer builds his teaching profession, in order to understand issues about training for teaching of engineering in higher education and how the professional career of Professor Engineer contributes to the building of professionalism and identity the teacher. At first, the research turned to the Education area of studies in Engineering and discussions being held on the teacher's professional development engineer in this area. For this, we used to reading articles published in Revista de Ensino de Engenharia, Journal of Engineering Education, European Journal of Engineering Education, in addition to papers published in the Annals of the Brazilian Congress of Engineering Education. Based on the literature review of the subject, it was made the study of theoretical contribution of renowned researchers in the field of Education, among them pepper and Anastasiou, Imbernon, Marcelo Garcia, Masetto, Almeida, Contreras and Cunha. The method for the collection of qualitative research used semi-structured interviews, based on the studies of Szymanski. Interviews were conducted with three teacher¿s engineers of a public university in the state of Rio de Janeiro. For transcription and categorization of data we used the Atlas Ti software. The initial data analysis was supported by Bardin, such as content analysis technique. To support the methodological point of view, Bardin, Franco, Szymanski, Sanchez Gamboa and Stake gave the necessary theoretical support. Based on the results of the interviews were made, initially, three categories of analysis: 1) teacher engineer training and the beginning of teaching; 2) the challenges and difficulties of the development of the teaching profession; and 3) the new challenges of teacher engineer and the construction of identity and the teaching profession. The survey results showed that the process of building the teaching profession teacher engineer occurs during practice, between hits and misses, considering that lack oriented training for teachers. Also showed that the difficulties and challenges that engineers face when teachers enter the teaching profession are being settled with the teaching time and experience in the classroom. However, new demands and new challenges are ever toward engineers to teachers, which has required new solutions and the creation of institutional spaces dedicated to improving the training of these teachers.